Trähägn en tänkbar metod för viltskydd i Svenskt skogsbruk? - Stenström, Olof; Nordel, Victor (SLU/Southern Swedish Forest Research Centre, 2010)
This survey was made to investigate the possibility of using an alternative method of fencing in Swedish forestry. The most common way of fencing in Sweden today is made by a two meter high metal net that is attached to turned impregnated poles. The fencing methods that have been investigated is a fencing system made completely out of wood so called “German wood fence”. Browsing of game in forest regeneration areas is often a big problem and some kind of protection of the plants is often necessary. There is several ways of building fences and the most common way is to use metal nets and impregnated poles, this leads to a problem when the fence has profiled its purpose. The net and the poles has to be removed out of the forest which is expensive and don’t give the landowner any income. In the spring of 2007 we were in Germany on an internship, there we came in contact with “German wood fencing”. During our visit we also had the opportunity to build one fence with this method. This became the starting point of this thesis that has been written in the spring of 2010. In our work with this thesis we also made a fieldtrip back to Germany and the Forstliches Bildungs Zentrum in Münchehof. During our trip we did inventory in Forstamt Sessen and Forstamt Saupark on this wood fencing system, we also revisited to the fence we built in 2007. We did interviews and had discussions with forest managers, forest workers and others with expertise. The districts that we visited in Germany have almost stopped fencing with metal net because the cost to bring the fence down is considered too expensive. They use instead this wood fencing system. We have studied the conditions for fencing in Sweden and the literature on the subject. Contacts have been taken with fencing entrepreneurs to learn what problem they have in their work and what their cost are. To build steal net fences is expensive and if the ground has to be flattened before the fence can be built the cost will increase. Manny of the entrepreneurs that we have been in contact with have built allot of fences and expect a problem in the future that weary few are taken down. Wood fences have benefits but further investigation is needed to see if the system is adjustable to Swedish conditions and demands. The biggest benefit is that the landowner don’t have to remove the fence when it have fulfilled its purpose, since the hole construction is built out of wood it will decay with time. One problem for alternative fencing systems are the Swedish National board off forestry’s criteria on how a fence should be constructed so the land owner can apply for subsidies of building the fence. Today can forest owner not expect to get any financial support from the National Board of Forestry for protecting their regeneration if they use wood fence. The criteria’s can be change if it is shown with studies that the system works.